High-crystallinity high-silicon mordenite as well as preparation method and application thereof
By adding a second silicon source and structural guide to the colloid for secondary crystallization, the upper limit of silicon-aluminum ratio of high silicon mordenite was successfully broken, and the synthesis of high crystallinity and high yield was achieved, the problems of silicon-aluminum atom loss and heterocrystal formation were solved, and catalytic activity and stability were improved.
Patent Information
- Application Number
- CN202311219794.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-20
AI Technical Summary
It is difficult to prepare high silicon mordenites with high crystallinity and high yields in the prior art. Especially when the silicon-aluminum ratio Si/Al>15, there are problems of silicon-aluminum atom loss and heterocrystal formation, which affects catalytic activity and stability.
By adding a second silicon source and structural guide to the original colloid with low Si/Al ratio, performing secondary crystallization, regulating the composition distribution of the skeleton silicon-aluminum atoms, breaking through the upper limit of the silicon-aluminum ratio, and achieving the synthesis of high crystallinity and high silicon mordenite.
It has achieved high crystallinity and high yield of high silicon mordenite, improved catalytic activity and stability, solved the problems of silicon atom activation and alkalinity control, and expanded the prospects for catalytic application.
Smart Images

Figure CN119660762A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of artificially synthesized mordenite, and more specifically to a high-crystallinity high-silicon mordenite and a preparation method and application thereof. Background Art
[0002] Mordenite is a common natural zeolite mineral in nature. Its pore structure consists of one-dimensional 12-membered ring channels and one-dimensional 8-membered ring channels. It has been widely used and studied as an adsorbent. In recent years, mordenite has attracted widespread attention from researchers as a catalytic material. Whether it is naturally formed or artificially synthesized, the MOR topological configuration is usually aluminum-rich and contains a high / Lewis acid center ratio, which is conducive to the electrophilic activation of the benzene ring and the formation of carbon cations. It has shown high catalytic activity and stability in catalyzing hydrocarbon reactions. It is a catalytic material with great application prospects. It has been industrially applied in reactions such as toluene disproportionation. It has also been widely studied in many chemical applications such as methanol amination.
[0003] The catalytic active centers of molecular sieves are affected by many factors. It is generally believed that they are closely related to the molecular sieve framework composition, structure and surface properties. The number of active centers is generally proportional to the content of aluminum atoms in the framework. In particular, the quantitative information of the framework crystallographic T site and the coordination chemical environment largely determine the type and properties of the catalytically active solid acid center.
[0004] Therefore, for catalytic reactions that require specific acid strength, it is necessary to develop mordenite with a corresponding silicon content. However, the literature reports that the silicon-aluminum molar ratio (Si / Al) of in-situ synthesized mordenite is usually less than 10. This framework composition affects the acid strength of the hydrogen-type zeolite. The effect of mixing the mixture gel chemistry on broadening the silicon-aluminum ratio range of the above-mentioned molecular sieve products is limited. The yield and crystallinity are easily significantly affected by the high silicon composition, and it is easy to be accompanied by dense phase impurities under the strong base synthesis system; at the same time, the controllability of regulatory means such as additives is poor, and it is difficult to achieve stable industrial production. Limited by the high nucleation activation energy, adding an appropriate amount of structure directing agent to form a charge density mismatch system can improve the framework silicon-aluminum ratio of the product mordenite, but it is still difficult to break through the bottleneck of Si / Al>15. The seed method or directing agent method synthesis cannot fundamentally improve the above problems.
[0005] In summary, due to the limitations of the effective activation of silicon atoms in a high-silicon composition environment, and the limitations of stability factors such as the bond angle and bond energy of the aluminum-containing skeleton, either too high or too low alkalinity is extremely unfavorable for the synthesis of high-crystalline, high-silicon mordenite with a one-dimensional pore skeleton. The in situ direct synthesis of high-silicon (Si / Al>15) mordenite is a recognized problem in the research and industrial communities, and is also a key technical challenge that needs to be urgently solved in the application of efficient solid acid catalysis. If the loss of silicon and aluminum atoms or the formation of impurities can be avoided to increase the silicon content of the mordenite skeleton, and provide more suitable active acid catalytic centers, it will have great prospects for industrial application. Summary of the invention
[0006] The object of the present invention is to provide a high-crystallinity high-silicon mordenite and a preparation method and application thereof, so as to solve the technical problem that it is difficult to prepare high-crystallinity and high-yield high-silicon mordenite in the prior art.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] In a first aspect, the present invention provides a mordenite, wherein Si / Al>15 and relative crystallinity>75% in the mordenite.
[0009] It should be noted that Si / Al used in the present invention represents the molar ratio of Si element to Al element.
[0010] According to some embodiments of the present invention, in the mordenite, 15<Si / Al≤20.
[0011] According to some embodiments of the present invention, in the mordenite, 15<Si / Al≤18.
[0012] According to some embodiments of the present invention, the relative crystallinity of the mordenite is >80%.
[0013] According to some embodiments of the present invention, the acid strength of the mordenite is shown as a desorption peak temperature of >355°C in temperature-programmed ammonia desorption (NH3-TPD).
[0014] According to some embodiments of the present invention, the acid strength of the mordenite is shown as a desorption peak temperature of 380-550° C. in temperature-programmed ammonia desorption (NH 3 -TPD).
[0015] According to some embodiments of the present invention, the acid strength of the mordenite is shown as a desorption peak temperature of 400-515° C. in temperature-programmed ammonia desorption (NH 3 -TPD).
[0016] In order to understand the acidity of solid acid catalysis, ammonia temperature-programmed desorption (NH3-TPD) is usually used for characterization. For example, it can be measured on an Altamira AMI-3300 chemical adsorption instrument produced by Micrometrics Instruments, Inc., USA. The obtained temperature-programmed ammonia desorption curve has characteristic peaks at different desorption temperatures, corresponding to different acid strengths. The higher the desorption temperature corresponding to the characteristic peak, the greater the acid strength.
[0017] According to some embodiments of the present invention, the specific surface area S of the mordenite BET ≥400m 2 / g, micropore volume V micro >0.15cm 3 / g.
[0018] According to some embodiments of the present invention, the specific surface area S of the mordenite BET 400~500m 2 / g, micropore volume V micro 0.19~0.25cm 3 / g.
[0019] The mordenite provided by the present invention breaks through the existing silicon-aluminum ratio by regulating the distribution of the silicon-aluminum atomic composition of the framework, has the characteristics of high acid strength and high crystallinity, and realizes the improvement of micropore diffusion, mass transfer and reaction performance of high-silicon mordenite.
[0020] In a second aspect, the present invention provides a method for preparing mordenite, comprising:
[0021] S1. Obtaining a colloid comprising a first silicon source, an aluminum source, an alkali source, a template R, and a solvent I; the molar ratio of the silicon element in the first silicon source to the aluminum element in the aluminum source is not greater than 15 (Si / Al≤15), preferably 5 to 15 (Si / Al=5 to 15);
[0022] S2. crystallizing the colloid to obtain a crystallized slurry;
[0023] S3. Adding a second silicon source and a structure directing agent SDA to the crystallization slurry so that the molar ratio of silicon to aluminum in the entire reaction system is greater than 15 (Si / Al>15);
[0024] S4. Performing secondary crystallization to obtain the mordenite;
[0025] Optionally, the method further comprises S5. calcining the mordenite for the first time, performing ion exchange, and then calcining for the second time.
[0026] The preparation method of mordenite provided by the present invention comprises the following steps: firstly mixing an aluminum source, an alkali source, a first silicon source, a template agent and a solvent, and performing a first crystallization according to a conventional low Si / Al ratio to obtain any one of mordenite, ZSM-5 molecular sieve, MCM-22 molecular sieve and β molecular sieve with high crystallinity, and then adding a second silicon source and a structure directing agent. If necessary, an appropriate amount of solvent can be added, and by strengthening the atomic coordination and bonding ability, a high-crystallinity and high-silicon mordenite can be obtained through a second crystallization.
[0027] In step S3, it can be determined whether it is necessary to add an appropriate amount of solvent I to the crystallization slurry according to the state of the crystallization slurry. Whether it is necessary to add solvent I and the specific amount of solvent I to be added are easily known to those skilled in the art.
[0028] In the preparation method provided by the present invention, the selection of raw material composition and conditions in the first crystallization and the addition of the second silicon source and the structure directing agent SDA have a relatively important influence on the crystallization degree of mordenite. The crystallization degree of mordenite can be improved by optimizing the synthesis ratio, improving the activity of the second silicon source and selecting a suitable structure directing agent SDA.
[0029] According to some embodiments of the present invention, the first silicon source and the second silicon source are the same or different, and are independently selected from at least one of silicon powder, silicon balls, silica gel, silica sol, sodium silicate (sodium silicate / water glass), silica alumina, silicates (such as methyl silicate, ethyl silicate, propyl silicate, etc.), silicon tetrachloride, silane (such as tetramethylsilane, methyltrimethoxysilane, isobutylene triethoxysilane, trichlorosilane, tetraethoxysilane, etc.), white carbon black, and diatomaceous earth.
[0030] According to some embodiments of the present invention, the second silicon source is selected from at least one of silica gel, silica sol, sodium silicate (sodium silicate / water glass), silica alumina, silicates (such as methyl silicate, ethyl silicate, propyl silicate, etc.), silicon tetrachloride, silanes (such as tetramethylsilane, methyltrimethoxysilane, isobutylenetriethoxysilane, trichlorosilane, tetraethoxysilane, etc.), and white carbon black.
[0031] According to some embodiments of the present invention, the aluminum source includes at least one of aluminum hydroxide, aluminum isopropoxide, aluminum sec-butoxide, sodium aluminate, aluminum sulfate, aluminum nitrate, aluminum chloride, and aluminum oxide.
[0032] According to some embodiments of the present invention, the alkali source includes alkali metal hydroxide and / or ammonia water; preferably, the alkali metal includes at least one of Li, Na, K, Rb, and Cs.
[0033] According to some embodiments of the present invention, the template R includes at least one of ammonia water, cycloheximide (HMI), piperidine, N,N,N-trimethyl-1-adamantyl ammonium bromide, pyridine, cyclopropylamine, cyclobutylamine, cyclooctylamine, cyclohexylmethylamine, ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, tripropylamine, n-butylamine, hexamethyleneimine, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, tetramethylammonium hydroxide, tetrapropylammonium iodide, tetraethylammonium iodide, tetrapropylammonium bromide, tetraethylammonium bromide, tetraethylammonium chloride or tetramethylammonium chloride.
[0034] According to some embodiments of the present invention, the solvent I includes at least one of deionized water, an alcohol solvent, and an imidazole-type ionic liquid.
[0035] According to some embodiments of the present invention, the solvent I includes at least one of deionized water, ethanol, isopropanol, glycerol, acetone, and n-butanol.
[0036] According to some embodiments of the present invention, the structure directing agent SDA includes at least one of tetraethylammonium hydroxide, tetraethylammonium chloride, tetraethylammonium bromide, and tetraethylammonium iodide.
[0037] According to some embodiments of the present invention, the molar ratio of the alkali source to the silicon element in the first silicon source is: OH - / Si=0.01 to 1, for example, 0.01, 0.03, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.33, 0.35, 0.38, 0.41, 0.45, 0.50, 0.6, 0.65, 0.7, 0.8, 0.85, 0.9, 0.95, 1, etc.
[0038] According to some embodiments of the present invention, the molar ratio of the solvent I to the silicon element in the first silicon source is: I / Si=5-50, for example, it can be 5, 6, 8, 10, 13, 15, 16, 19, 20, 23, 25, 26, 28, 30, 35, 38, 40, 44, 46, 50, etc.
[0039] According to some embodiments of the present invention, the molar ratio of the template R to the silicon element in the first silicon source is: R / Si=0.01-0.5, for example, it can be 0.01, 0.03, 0.05, 0.08, 0.1, 0.15, 0.2, 0.21, 0.25, 0.28, 0.3, 0.33, 0.35, 0.38, 0.41, 0.45, 0.47, 0.5, etc.
[0040] According to some embodiments of the present invention, the molar ratio of the structure directing agent SDA to the sum of the silicon elements in the first silicon source and the second silicon source is: SDA / Si=0.001-0.5, for example, it can be 0.001, 0.002, 0.003, 0.005, 0.007, 0.008, 0.009, 0.01, 0.015, 0.03, 0.05, 0.065, 0.08, 0.1, 0.15, 0.2, 0.21, 0.25, 0.28, 0.3, 0.33, 0.35, 0.38, 0.41, 0.45, 0.47, 0.5, etc.
[0041] According to some embodiments of the invention, the ion exchange comprises ammonium exchange.
[0042] According to some embodiments of the present invention, the ammonium exchange reagent includes at least one of ammonium nitrate, ammonium chloride, ammonium oxalate, and ammonium sulfate.
[0043] According to some embodiments of the present invention, the ammonium exchange is carried out at a temperature of 10 to 120° C. for 0.1 to 1000 h, preferably at a temperature of 50 to 80° C. for 0.5 to 5 h.
[0044] According to some embodiments of the present invention, the concentration of the aqueous solution of the ammonium exchange reagent is 0.01 to 5 mol / L.
[0045] According to some embodiments of the present invention, the volume mass ratio of the aqueous solution of the ammonium exchange reagent to the mordenite is 4-10 mL:1 g.
[0046] According to some embodiments of the present invention, the number of ion exchanges is 1 to 20 times, preferably 2 to 6 times.
[0047] According to some embodiments of the present invention, after the ion exchange, filtering, washing and drying are first performed, and then a secondary calcination is performed; preferably, the drying temperature is 30 to 200° C., preferably 80 to 120° C., and the time is 0.1 to 1000 h, preferably 0.5 to 10 h.
[0048] According to some embodiments of the present invention, the stirring speed of the primary crystallization is 0-6000 rpm, preferably 10-100 rpm, the crystallization temperature is 80-200° C., preferably 120-180° C., and the crystallization time is 2-2000 hours, preferably 100-300 hours.
[0049] According to some embodiments of the present invention, pre-crystallization is performed before the primary crystallization, and the pre-crystallization temperature is 70 to 140° C. and the time is 2 to 10 hours.
[0050] According to some embodiments of the present invention, the stirring speed of the secondary crystallization is 0-6000 rpm, preferably 10-100 rpm, the crystallization temperature is 80-200° C., preferably 120-180° C., and the crystallization time is 2-2000 hours, preferably 100-300 hours.
[0051] According to some embodiments of the present invention, pre-crystallization is performed before the secondary crystallization, and the pre-crystallization temperature is 70 to 140° C. and the time is 2 to 10 hours.
[0052] According to some embodiments of the present invention, after the secondary crystallization, filtering, washing and drying steps are further included; preferably, the drying temperature is 30 to 200° C., preferably 80 to 120° C., and the drying time is 0.1 to 1000 h, preferably 0.5 to 10 h.
[0053] According to some embodiments of the present invention, the temperature of the first calcination is 200 to 980° C., preferably 400 to 650° C., and the time of the first calcination is 0.1 to 250 h, preferably 1 to 10 h.
[0054] According to some embodiments of the present invention, the temperature of the second calcination is 400-650° C., preferably 500-550° C.; the time of the second calcination is 1-10 h.
[0055] According to some embodiments of the present invention, the second calcination is carried out in a staged calcination manner, including: calcining at a temperature of 150-200°C for 0.5-3h, then calcining at a temperature of 250-350°C for 0.5-3h, then calcining at a temperature of 400-500°C for 0.5-3h, and finally calcining at a temperature of 200-900°C for 0.1-100h.
[0056] In a third aspect, the present invention provides a mordenite prepared by the preparation method described in the second aspect.
[0057] In a fourth aspect, the present invention provides use of the mordenite described in the first aspect or the mordenite described in the third aspect in aromatic hydrocarbon conversion.
[0058] According to some embodiments of the present invention, the weight space velocity of aromatics in the aromatics conversion is 0.01 to 50 h -1 , the hydrogen-to-oil molar ratio is 0-300.
[0059] The mordenite provided by the present invention has the characteristics of high crystallinity and high silicon, is a solid acid catalytic material with a unique structure, has a large specific surface area and strongly acidic external surface active centers, exhibits very excellent adsorption and activation properties for aromatic molecules, can provide more suitable active sites for aromatic conversion, and is used for catalyzing aromatic conversion with the characteristics of high selectivity, high activity and high stability.
[0060] According to some embodiments of the present invention, the application includes application in an aromatic hydrocarbon dealkylation reaction, such as application in a trimethylbenzene selective dealkylation reaction.
[0061] According to some embodiments of the present invention, the temperature of the trimethylbenzene selective dealkylation reaction is 250-650° C. and the pressure is 0-20 MPa.
[0062] In a fifth aspect, the present invention provides an aromatic hydrocarbon conversion catalyst, wherein the catalyst comprises the mordenite described in the first aspect or the mordenite described in the third aspect.
[0063] According to some embodiments of the present invention, the catalyst further comprises an active component.
[0064] According to some embodiments of the present invention, the active component includes at least one of Group IIIA alumina metals, Group IVA metals, Group VA metals, transition metals (including Groups IB to VIIB metals, and Group VIII metals).
[0065] According to some embodiments of the present invention, the active component is selected from at least one of Y, La, Ce, Pr, Nd, Fe, Co, and Ni.
[0066] According to some embodiments of the present invention, the catalyst comprises a reduction step prior to the reaction.
[0067] According to some embodiments of the present invention, the reduction is carried out by hydrogen reduction, wherein the hydrogen flow rate is 8 to 800 mL / min; during the reduction, the temperature is first increased to 100 to 280°C at a rate of 0.1 to 20°C / min and kept constant at this temperature for 0 to 48 hours, and then the temperature is increased to 300 to 750°C at a rate of 0.1 to 50°C / min and kept constant at this temperature for 0 to 48 hours.
[0068] The beneficial effects of the present invention are at least:
[0069] The present invention aims at the technical difficulty that mordenite is difficult to form a high-silicon skeleton. After adding a second silicon source and a structure directing agent, the second crystallization is carried out to achieve the control of the skeleton composition of the mordenite, expand the flexibility of the high-silicon skeleton, optimize the skeleton bending force constant, reduce the structural stress and achieve the coordination stabilization effect, solve the problem of silicon atom induced activation, and achieve the precise construction of high-crystallinity high-silicon mordenite. It solves the technical bottleneck that it is difficult to directly synthesize high-silicon mordenite by a single gel crystallization and the problems of low crystallization activity and poor uniformity under conditions of too high or too low alkalinity, breaks through the upper limit of the Si / Al ratio phase region of the artificial in-situ synthesis of mordenite, effectively controls crystal parameters and improves product yield, thereby enhancing the microporous crystallinity of the zeolite, greatly optimizing the metastable surface active acid center distribution of the zeolite, and having good aromatics conversion performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 The XRD spectrum of high-crystalline high-silicon mordenite prepared in Example 1 of the present invention;
[0071] Figure 2 This is a SEM photo of high-crystallinity high-silicon mordenite obtained in Example 1 of the present invention;
[0072] Figure 3 This is a HR-TEM photograph of the high-silicon mordenite obtained in Example 1 of the present invention.
[0073] Figure 4 This is the NH3-TPD curve of the high-silicon mordenite obtained in Example 1 of the present invention.
[0074] Figure 5 This is the N2 adsorption-desorption curve of the high-silicon mordenite prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0075] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.
[0076] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0077] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.
[0078] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0079] In each embodiment and comparative example of the present invention, each performance data is tested according to the following test method:
[0080] (1) Phase analysis (XRD spectrum): measured using a Bruker D8Focus diffractometer with a graphite monochromator, a Cu target Kα ray source, a wavelength λ of 0.154 nm, a tube voltage of 40 kV, a tube current of 40 mA, and recording diffraction signals in the 2θ range of 3-90° (scanning speed of 2° / min).
[0081] (2) Scanning electron imaging (SEM) images: taken using a FEI Nova Nano SEM 450 microscope.
[0082] (3) Spherical aberration transmission imaging (TEM) photos: taken using a FEI Tecnai 20S-Twin microscope.
[0083] (4) The ammonia temperature-programmed desorption (NH3-TPD) curve signal information was collected using an Altamira AMI-3300 chemical adsorption instrument produced by Micrometrics.
[0084] (5) The molecular sieve samples were characterized by low-temperature N2 adsorption-desorption using a 3Flex-Physisorption analyzer produced by Micrometrics. The test temperature was 77 K. The specific surface area and pore structure parameters were calculated by analyzing the isotherms using the BET method and the BJH method.
[0085] (6) Silicon-to-aluminum ratio of test samples: The test samples were dissolved in HF aqueous solution at room temperature and then quantitatively analyzed on an Optima 3300DV inductively coupled plasma emission spectrometer (ICP) from PerkinElmer, USA.
[0086] In each embodiment and comparative example of the present invention, the polytetrafluoroethylene-lined pressure steel autoclave used was purchased from Shandong Yantai Muping Shuguang Precision Instrument Factory, with a specification of 100 mL; the rotary oven was purchased from a 200L space rotary oven produced by Beijing Creaser Company.
[0087] Example 1
[0088] A high-crystallinity high-silicon mordenite, the synthesis method is as follows:
[0089] First, NaOH and sodium aluminate were dissolved in deionized water, followed by the addition of hexamethyleneimine (template agent R, 25 wt% aqueous solution), and finally the addition of silicon source methyl silicate, wherein the silicon source (in terms of Si content), template agent R, aluminum source (in terms of Al content), alkali source (in terms of OH content) - The molar ratio of 2-nitrogen (methylenediamine) and deionized water is 25:5:4:0.75:250, and a milky white gel solution is obtained after being evenly stirred; the gel solution is then placed in a polytetrafluoroethylene-lined pressure steel autoclave, pre-crystallized for 6 hours at a temperature of 90°C, and then placed in a rotary oven at a temperature of 150°C and a rotation speed of 20 rpm for further hydrothermal crystallization for 200 hours, and then cooled to room temperature with tap water to obtain a crystallization slurry of pure phase MCM-22 (MWW configuration) with high crystallinity;
[0090] Add appropriate amounts of silicon source ethyl silicate, tetraethylammonium hydroxide (structure directing agent SDA, 25wt% aqueous solution) and deionized water to the crystallization slurry, so that the molar ratio of silicon source (in terms of Si content), R+SDA, aluminum source (in terms of Al content), alkali source (in terms of OH-) and deionized water in the reaction system is 66:8:4; 0.75:680; repeat the above crystallization procedure for secondary crystallization, cool to room temperature with tap water, filter and wash the product, and dry it in an oven at 100°C for 2h to obtain zeolite raw powder.
[0091] The zeolite powder was tested, among which the XRD test was shown in Figure 1 It can be seen that it is a pure phase MOR configuration with a relative crystallinity of 83%. SEM and TEM photos are shown in Figure 2 and Figure 3 The Si / Al ratio of this sample is 16.3, and the specific surface area S BET 442m 2 / g, micropore volume V micro 0.19cm 3 / g.
[0092] The zeolite raw powder was calcined at 550℃ for 2h and then cooled, and then the zeolite raw powder was subjected to ion exchange and secondary calcination. Specifically, the calcined zeolite raw powder and 1 mol / L ammonium chloride aqueous solution were mixed at a solid (mass, g) to liquid (volume, mL) ratio of 1:6, and heated in a water bath to 65℃ for 1h for ion exchange; then filtered and washed with deionized water, and the above process was repeated 4 times to obtain a filter cake, which was dried in an oven at 100℃ for 2h to obtain NH4 + The zeolite was calcined at 520℃ for 3h to obtain the hydrogen type molecular sieve, and the obtained mordenite was recorded as GM1. The temperature-programmed ammonia desorption NH3-TPD curve showed that the desorption peak temperature of the sample was 491.5℃.
[0093] Example 2
[0094] A high-crystallinity high-silicon mordenite, the synthesis method is as follows:
[0095] First, CsOH and sodium aluminate are dissolved in deionized water, then tetraethylammonium hydroxide (template R, 25wt% aqueous solution) is added, and finally silicon source methyl silicate is added, wherein the molar ratio of silicon source (in terms of Si content), template R, aluminum source (in terms of Al content), alkali source (in terms of OH-) and deionized water is 25:12:2:1.25:200, and a milky white gelling solution is obtained after being stirred evenly; then the gelling solution is charged into a pressure steel autoclave lined with polytetrafluoroethylene, pre-crystallized for 6 hours at a temperature of 90°C, and then placed in a rotary oven at a temperature of 150°C and a rotation speed of 20rpm for further hydrothermal crystallization for 200 hours, and then cooled to room temperature with tap water to obtain a crystallization slurry of high-crystallinity β molecular sieve;
[0096] Add appropriate amounts of silicon source white carbon black, tetraethylammonium chloride (structure directing agent SDA, 25wt% aqueous solution) and deionized water to the crystallization slurry, so that the molar ratio of silicon source (in terms of Si content), R+SDA, aluminum source (in terms of Al content), alkali source (in terms of OH-) and deionized water in the reaction system is 35:14:2; 1.25:500; repeat the above crystallization procedure for secondary crystallization, cool to room temperature with tap water, filter and wash the product, and dry it in an oven at 100°C for 2h to obtain zeolite raw powder.
[0097] Test the zeolite powder.
[0098] Among them, the XRD test results show that the obtained sample is a pure phase MOR configuration, and the relative crystallinity reaches 81%. SEM photos and TEM photos show that the high-silicon molecular sieve sample has good microporous crystallinity. The Si / Al ratio of the sample is 15.9, and the specific surface area S BET 405m 2 / g, micropore volume V micro 0.21cm3 / g.
[0099] The zeolite raw powder was calcined at 550℃ for 2h and then cooled, and then the zeolite raw powder was subjected to ion exchange and secondary calcination. Specifically, the calcined zeolite raw powder and 1 mol / L ammonium chloride aqueous solution were mixed at a solid (mass, g) to liquid (volume, mL) ratio of 1:5, and heated in a water bath to 65℃ for 1h for ion exchange; then filtered and washed with deionized water, and the above process was repeated 4 times to obtain a filter cake, which was dried in an oven at 100℃ for 2h to obtain NH4 + The zeolite was calcined at 520℃ for 3h to obtain the hydrogen type molecular sieve, and the obtained mordenite was recorded as GM2. The temperature-programmed ammonia desorption NH3-TPD curve showed that the desorption peak temperature of the sample was 450℃.
[0100] Example 3
[0101] A high-crystallinity high-silicon mordenite, the synthesis method is as follows:
[0102] First, KOH and ammonia (K + :NH4 + 2) and aluminum isopropoxide are dissolved in deionized water, followed by the addition of tetrapropylammonium bromide (template agent R, 25 wt% aqueous solution), and finally the addition of silicon source trichlorosilane, wherein the silicon source (in terms of Si content), R, aluminum source (in terms of Al content), alkali source (in terms of OH - The molar ratio of ZSM-5 and deionized water is 16:5:2:5:450, and a milky white gel solution is obtained after uniform stirring; the gel solution is then charged into a polytetrafluoroethylene-lined pressure steel autoclave, pre-crystallized for 6 hours at a temperature of 90°C, and then placed in a rotary oven at a temperature of 150°C and a rotation speed of 20rpm for further hydrothermal crystallization for 160 hours, and then cooled to room temperature with tap water to obtain a crystallization slurry of ZSM-5 and mordenite zeolite intergrowth molecular sieve.
[0103] Add appropriate amounts of silicon source methyl silicate, tetraethylammonium iodide (structure directing agent SDA, 25wt% aqueous solution) and deionized water to the crystallization slurry to make the silicon source (in terms of Si content), R+SDA, aluminum source (in terms of Al content), alkali source (in terms of OH content) in the reaction system. - The molar ratio of zeolite to deionized water is 40:8:2:5:780; the above crystallization procedure is repeated for secondary crystallization, and the product is cooled to room temperature with tap water. The product is filtered, washed, and dried in an oven at 100°C for 2h to obtain zeolite raw powder.
[0104] The zeolite powder was tested, and the XRD test results showed that the obtained sample was a pure phase MOR configuration with a relative crystallinity of 87%. SEM and TEM photos showed that the high-silicon molecular sieve sample exhibited good microporous crystallinity. The Si / Al ratio of the sample was 16.5, and the specific surface area S BET 435m 2 / g, micropore volume V micro 0.20cm 3 / g.
[0105] The process of preparing mordenite using zeolite raw powder is referred to Example 1, and the obtained mordenite is recorded as GM3. The temperature-programmed ammonia desorption NH3-TPD curve shows that the desorption peak temperature of the sample is 455°C.
[0106] Example 4
[0107] A high-crystallinity high-silicon mordenite, the synthesis method is as follows:
[0108] First, RbOH and aluminum sec-butoxide are dissolved in deionized water, then n-butylamine (template agent R) is added, and finally silicon source isobutylene triethoxysilane is added, wherein silicon source (in terms of Si content), R, aluminum source (in terms of Al content), alkali source (in terms of OH content) are added. - The molar ratio of 2-nitrogen (2-nitrogen) and deionized water is 20:4:3.5:1.4:900, and a milky white gel solution is obtained after being evenly stirred; the gel solution is then placed in a polytetrafluoroethylene-lined pressure steel autoclave, pre-crystallized for 6 hours at a temperature of 90°C, and then placed in a rotary oven at a temperature of 150°C and a rotation speed of 20 rpm for further hydrothermal crystallization for 160 hours, and then cooled to room temperature with tap water to obtain a crystallized slurry of ZSM-5 molecular sieve;
[0109] Add appropriate amounts of silicon tetrachloride, tetraethylammonium hydroxide (structure directing agent SDA, 25 wt% aqueous solution) and deionized water to the crystallization slurry to make the silicon source (in terms of Si content), R+SDA, aluminum source (in terms of Al content), alkali source (in terms of OH content) in the reaction system. - The molar ratio of 2-nitrogen (calculated) and deionized water is 56:5:3.5:2:1400; the above crystallization procedure is repeated for secondary crystallization, and the product is cooled to room temperature with tap water. The obtained product is filtered, washed, and dried in an oven at 100°C for 2h to obtain zeolite raw powder.
[0110] The zeolite powder was tested, and the XRD test results showed that the obtained sample was a pure phase MOR configuration with a relative crystallinity of 82%. SEM and TEM photos showed that the high-silicon molecular sieve sample exhibited good microporous crystallinity. The Si / Al ratio of the sample was 15.2, and the specific surface area S BET 409m 2 / g, micropore volume V micro0.21cm 3 / g.
[0111] The zeolite raw powder was calcined at 550℃ for 2h and then cooled, and then the zeolite raw powder was ion exchanged and calcined again. Specifically, the calcined zeolite raw powder and 1mol / L ammonium chloride aqueous solution were mixed at a solid (mass, g) to liquid (volume, mL) ratio of 1:4, and heated to 65℃ in a water bath for 1h for ion exchange; then filtered and washed with deionized water, and the above process was repeated 4 times to obtain a filter cake, which was dried in an oven at 100℃ for 2h to obtain an NH4+ type molecular sieve, and calcined at 520℃ for 3h to obtain a hydrogen type molecular sieve. The obtained mordenite was recorded as GM4. The programmed temperature ammonia desorption NH3-TPD curve showed that the desorption peak temperature of the sample was 515℃.
[0112] Example 5
[0113] A high-crystallinity high-silicon mordenite, the synthesis method of which is the same as that of Example 1, except that the ethyl silicate added to the slurry is replaced with diatomaceous earth in an equal molar amount (calculated as Si element).
[0114] After secondary crystallization, the product was filtered, washed and dried to obtain the original molecular sieve powder. The original molecular sieve powder was tested, and the XRD test results showed that the obtained sample was a pure phase MOR configuration with a relative crystallinity of 78%. SEM and TEM photos showed that the molecular sieve sample had good microporous crystallinity. Si / Al was 9.9, and the specific surface area S BET 416m 2 / g, micropore volume V micro 0.18cm 3 / g.
[0115] The process of preparing mordenite using zeolite raw powder is referred to Example 1, and the obtained mordenite is recorded as GM5. The temperature-programmed ammonia desorption NH3-TPD curve shows that the desorption peak temperature of the sample is 450°C.
[0116] Example 6
[0117] A high-crystallinity high-silicon mordenite, a high-crystallinity high-silicon mordenite, the synthesis method of which refers to Example 2, the only difference is that the white carbon black added to the slurry is replaced by an equimolar amount (calculated as Si element) of silicon powder.
[0118] After secondary crystallization, the product was filtered, washed and dried to obtain the original molecular sieve powder. The original molecular sieve powder was tested, and the XRD test results showed that the obtained sample was a pure phase MOR configuration with a relative crystallinity of 80%. SEM and TEM photos showed that the molecular sieve sample had good microporous crystallinity. Si / Al was 14.6, and the specific surface area S BET401m 2 / g, micropore volume V micro 0.17cm 3 / g.
[0119] The process of preparing mordenite using zeolite raw powder is referred to Example 2, and the obtained mordenite is recorded as GM6. The temperature-programmed ammonia desorption NH3-TPD curve shows that the desorption peak temperature of the sample is 425°C.
[0120] Example 7
[0121] A high-crystallinity and high-silicon mordenite is synthesized by the same method as in Example 1, except that tetraethylammonium hydroxide is replaced by an equimolar amount of hexamethyleneimine.
[0122] After secondary crystallization, the product was filtered, washed and dried to obtain the original molecular sieve powder. The original molecular sieve powder was tested, and the XRD test results showed that the obtained sample was a pure phase MOR configuration with a relative crystallinity of 79%. SEM and TEM photos showed that the molecular sieve sample exhibited good microporous crystallinity. Si / Al was 15.9, and the specific surface area S BET 428m 2 / g, micropore volume V micro 0.19cm 3 / g.
[0123] The process of preparing mordenite using zeolite raw powder is referred to Example 1, and the obtained mordenite is recorded as GM7. The temperature-programmed ammonia desorption NH3-TPD curve shows that the desorption peak temperature of the sample is 390°C.
[0124] Comparative Example 1
[0125] A mordenite, the synthesis method of which is the same as that of Example 1, except that only one feeding is used, so that the molar ratios of silicon source (methyl silicate + ethyl silicate, calculated by Si content), R + SDA, aluminum source (calculated by Al content), (NaOH and sodium bromide) and deionized water in the reaction system are 66:8:4; 0.75:680, and only one crystallization is used. The obtained mordenite is recorded as DM1.
[0126] The zeolite raw powder of this comparative example was tested, and the results showed that it was a pure phase MOR configuration; Si / Al was 7, the crystallinity was low, and the specific surface area S BET 195m 2 / g, micropore volume V micro 0.11cm 3 / g, the specific surface area and micropore volume are both low, and the morphology is irregular and large.
[0127] Catalytic performance evaluation
[0128] The mordenite prepared in each example and comparative example was made into a catalyst, and its catalytic performance was tested.
[0129] The mordenite prepared in each embodiment and comparative example was shaped into φ1mm×1mm particles; 800g was weighed, mixed evenly with 8g of an active component solution with a mass concentration of 5%, and then allowed to stand and impregnate for 12h at room temperature; the impregnated mordenite was then transferred to an oven and dried at a temperature of 110°C for 3h; the dried mordenite was then calcined at a temperature of 500°C for 3h in an air atmosphere to obtain a catalyst.
[0130] Take 5g of each of the above catalysts and load them into a stainless steel fixed bed tubular reactor, and reduce them with pure hydrogen. The reduction conditions are as follows: hydrogen flow rate 80mL / min, heating to 180℃ at 2℃ / min and keeping constant temperature for 2h, then heating to 375℃ at 2.5℃ / min and keeping constant temperature for 2h. Add raw material trimethylbenzene for selective dealkylation reaction, and the product is analyzed by HP6890 gas chromatography. Reaction conditions: reaction temperature 375℃, reaction pressure 0.6MPa, raw material weight space velocity 3.35h -1 , hydrogen to oil molar ratio 3. The online 100h reaction results are shown in Table 1.
[0131] Activity (conversion rate C) and BTX selectivity (yield of high-quality low-carbon aromatics) are used as catalyst performance evaluation indicators.
[0132]
[0133] (TMB stands for trimethylbenzene, including 1,2,4-trimethylbenzene, 1,3,5-mesitylene and mixtures)
[0134] S BTX =(BTX in product / Σproduct)×100%
[0135] (B stands for benzene, T stands for toluene, and X stands for xylene)
[0136] Table 1
[0137]
[0138]
[0139] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A mordenite, characterized in that: The Si / Al ratio of the mordenite is greater than 15, and the relative crystallinity is greater than 75%.
2. The mordenite according to claim 1, characterized in that In the mordenite, 15<Si / Al≤20; And / or, the acid strength is shown as a desorption peak temperature of programmed temperature ammonia desorption> 355°C; And / or, the specific surface area S of the mordenite BET ≥400m 2 / g, micropore volume V micro >0.15cm 3 / g.
3. A method for preparing mordenite, characterized in that: include: S1. Obtaining a colloid comprising a first silicon source, an aluminum source, an alkali source, a template R, and a solvent I; The molar ratio of the silicon element in the first silicon source to the aluminum element in the aluminum source is not greater than 15, preferably 5 to 15; S2. crystallizing the colloid to obtain a crystallized slurry; S3. Adding a second silicon source and a structure directing agent SDA to the crystallization slurry so that the molar ratio of silicon to aluminum in the entire reaction system is greater than 15; S4. Performing secondary crystallization to obtain the mordenite; Optionally, the method further comprises S5. calcining the mordenite for the first time, performing ion exchange, and then calcining for the second time.
4. The preparation method according to claim 3, characterized in that: The first silicon source and the second silicon source are the same or different, and are independently selected from at least one of silicon powder, silicon spheres, silica gel, silica sol, sodium silicate, silica alumina, silicate, silicon tetrachloride, silane, white carbon black, and diatomaceous earth; Preferably, the second silicon source is selected from at least one of silica gel, silica sol, sodium silicate, silica alumina, silicate, silicon tetrachloride, silane and white carbon black.
5. The preparation method according to claim 3 or 4, characterized in that: The aluminum source includes at least one of aluminum hydroxide, aluminum isopropoxide, aluminum sec-butoxide, sodium aluminate, aluminum sulfate, aluminum nitrate, aluminum chloride, and aluminum oxide; And / or, the alkali source includes alkali metal hydroxide and / or ammonia water; preferably, the alkali metal includes at least one of Li, Na, K, Rb, and Cs; And / or, the template R includes at least one of ammonia water, cyclohexylimine, piperidine, N,N,N-trimethyl-1-adamantyl ammonium bromide, pyridine, cyclopropylamine, cyclobutylamine, cyclooctylamine, cyclohexylmethylamine, ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, tripropylamine, n-butylamine, hexamethyleneimine, tetrapropylammonium hydroxide, tetraethylammonium hydroxide, tetramethylammonium hydroxide, tetrapropylammonium iodide, tetraethylammonium iodide, tetrapropylammonium bromide, tetraethylammonium bromide, tetraethylammonium chloride or tetramethylammonium chloride; And / or, the solvent I includes at least one of deionized water, alcohol solvents, and imidazole-type ionic liquids; preferably, the solvent I includes at least one of deionized water, ethanol, isopropanol, glycerol, acetone, and n-butanol; And / or, the structure directing agent SDA includes at least one of tetraethylammonium hydroxide, tetraethylammonium chloride, tetraethylammonium bromide and tetraethylammonium iodide.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The molar ratio of the alkali source to the silicon element in the first silicon source is: OH - / Si=0.01~1; And / or, the molar ratio of the solvent I to the silicon element in the first silicon source is: I / Si=5-50; And / or, the molar ratio of the template R to the silicon element in the first silicon source is: R / Si=0.01-0.5; And / or, the molar ratio of the structure directing agent SDA to the sum of silicon elements in the first silicon source and the second silicon source is: SDA / Si=0.001-0.
5.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The ion exchange comprises ammonium exchange; Preferably, The ammonium exchange reagent includes at least one of ammonium nitrate, ammonium chloride, ammonium oxalate, and ammonium sulfate; And / or, the ammonium exchange is carried out at a temperature of 10 to 120° C. for 0.1 to 1000 h; and / or, the concentration of the aqueous solution of the ammonium exchange reagent is 0.01 to 5 mol / L; And / or, the volume mass ratio of the aqueous solution of the ammonium exchange reagent to the mordenite is 4-10 mL:1 g.
8. The preparation method according to any one of claims 3 to 7, characterized in that: The number of ion exchanges is 1 to 20 times; And / or, after the ion exchange, filtering, washing and drying are first performed, and then secondary calcination is performed; preferably, the drying temperature is 30 to 200° C.; And / or, the stirring speed of the primary crystallization is 0 to 6000 rpm, the crystallization temperature is 80 to 200° C., and the crystallization time is 2 to 2000 hours; And / or, the stirring speed of the secondary crystallization is 0 to 6000 rpm, the crystallization temperature is 80 to 200° C., and the crystallization time is 2 to 2000 hours; And / or, after the secondary crystallization, the method further comprises filtering, washing and drying steps; preferably, the drying temperature is 30 to 200° C.; And / or, the temperature of the first calcination is 200-980° C., and the time of the first calcination is 0.1-250 h; And / or, the temperature of the second calcination is 400-650° C., and the time of the second calcination is 1-10 hours.
9. Use of the mordenite according to claim 1 or 2 or the mordenite prepared by the preparation method according to any one of claims 3 to 8 in aromatic hydrocarbon conversion.
10. An aromatic hydrocarbon conversion catalyst, characterized in that: The catalyst comprises the mordenite according to claim 1 or 2 or the mordenite prepared by the preparation method according to any one of claims 3-8.
Citation Information
Patent Citations
Isomorphous phase compound molecular sieve and preparation method thereof
CN102910645A
Preparation method of mordenite
CN104276586A
Mercerizing molecular sieve catalyst, preparation method and application thereof
CN107511166A
Preparation method and application of mordenite with high silica-alumina ratio
CN112537778A
Methods for preparing zeolites with surfactant-templated mesoporosity and tunable aluminum content
US20170190587A1